2020
DOI: 10.1002/jper.20-0310
|View full text |Cite
|
Sign up to set email alerts
|

Acellular dermal matrix for root coverage procedures: 9‐year assessment of treated isolated gingival recessions and their adjacent untreated sites

Abstract: Background The long‐term outcomes of acellular dermal matrix (ADM) for the treatment of isolated gingival recessions has not yet been evaluated. Thus, the aim of this study was to observe the root coverage outcomes of coronally advanced flap with ADM over time, and compare them with their adjacent untreated sites. Methods Twelve patients (from 20) were available at the 9‐year recall. Clinical parameters (recession depth, mean root coverage [mRC], keratinized tissue width [KTW], and gingival thickness) were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 46 publications
(88 reference statements)
0
38
0
1
Order By: Relevance
“…Although it has been well demonstrated that CAF + CTG is the gold standard treatment for root coverage procedures [6,7,9], patient morbidity, the need for a second surgical site, and limited availability are the main drawbacks of autogenous grafts [13,14,16]. Therefore, it is not surprising that several soft-tissue-graft substitutes and biologic agents have been explored in the last two decades for the treatment of gingival recessions [18,20,57,58]. Among them, platelet concentrates have progressively gained popularity among clinicians due to their properties of enhancing wound healing [19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been well demonstrated that CAF + CTG is the gold standard treatment for root coverage procedures [6,7,9], patient morbidity, the need for a second surgical site, and limited availability are the main drawbacks of autogenous grafts [13,14,16]. Therefore, it is not surprising that several soft-tissue-graft substitutes and biologic agents have been explored in the last two decades for the treatment of gingival recessions [18,20,57,58]. Among them, platelet concentrates have progressively gained popularity among clinicians due to their properties of enhancing wound healing [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent 12-year follow-up from an RCT by Tavelli and coworkers, GT ≥ 1.2 mm at the six-month follow-up is a predictor for the stability of the gingival margin over time [17]. Interestingly, Barootchi et al 2020 demonstrated that the augmented gingival thickness is sustained over time and is associated with a reduction in plaque index scores [18]. Therefore, although CTG remains the gold standard for increasing GT [18], we found that L-PRF resulted in significantly greater GT gain than CAF alone.…”
Section: Principal Findingsmentioning
confidence: 99%
“…While the importance of an experienced surgeon in treatment of PTSDs cannot be overstated, with regard to the use of a CTG, indeed its properties of enhancing blood clot, flap stability, increasing keratinized tissue width/soft tissue thickness, and the possibility of creeping attachment (Tavelli et al., 2019, 2020) have rendered it the gold standard for root coverage (Barootchi et al., 2019, 2020; Mazzotti et al., 2018; Zucchelli et al., 2019). Therefore, future studies are needed for further validation of IDES, including different flap designs (e.g., the tunnel approach; Aroca et al., 2013; Tavelli et al., 2018; Zuhr et al., 2014) and grafting materials (e.g., acellular dermal or collagen matrices; Barootchi, Tavelli, Gianfilippo, et al., 2020; Stefanini, Mounssif, et al., 2020), as well as execution by less proficient clinicians. Also, given the current pilot study design, we deem necessary future investigations with a larger number of examiners, as well as assessments by less experienced audience to test the consistency in ratings with the IDES, and indeed the relationship with a subjective approach.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, transgingival probing is one of the most common methods for assessing soft tissue thickness, as typically measured 1–3 mm apical to the soft tissue margin (Barootchi, Tavelli, Gianfilippo, et al, 2020; Barootchi, Tavelli, Zucchelli, et al, 2020; Tavelli, Barootchi, et al, 2020). However, this measurement does not represent the overall volumetric changes, but the variation in MT at a specific reference point (plane), which may not be representative of the overall volume gain/loss after a treatment.…”
Section: Discussionmentioning
confidence: 99%